Analysis of Return on Equity and DER on Economic Value Added at PT. BPRS Puduarta Insani Deli Serdang District - Nasution, Nina Andriany; Panggabean, Fitri Yani; Agustin, Khairani (The Es Accounting And Finance, 2024)
To analyze Return on Equity and DER (Debt to Equity Ratio) on Economic Value Added at PT. BPRS Puduarta Insani Deli Serdang District. Specifically, to analyze the measurement of Return on Equity (ROE) and DER on Economic Value Added (EVA). Uses Regression Data Type from 2016 - 2023, Multiple Linear Regression. The results are: 1) ROE has a positive and partially significant effect on EVA, because an increase in equity can increase the added value of positive EVA at PT. BPRS Puduarta Insani Deli Serdang; 2) DER has a negative and partially significant effect on EVA, because debt that exceeds the asset value can reduce the equity value. Low Equity will cause a negative EVA value at PT. BPRS Puduarta Insani Deli Serdang; 3) ROE and DER simultaneously have a positive and significant effect on EVA at PT. BPRS Puduarta Insani Deli Serdang District.